(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Primary neoplasms of the external ear canal are rare, and 5% of these tumors are of glandular origin. Ceruminal glands are modified sweat glands of the skin of the external auditory meatus that may give rise to (a) benign tumors such as ceruminous adenoma, pleomorphic adenoma, and syringocystadenoma papilliferum, and (b) malignant tumors such as ceruminous adenocarcinoma, adenoid cystic carcinoma, and mucoepidermoid carcinoma. An alternative theory holds that pleomorphic adenomas may well arise from ectopic salivary tissue present in the external ear canal. These tumors are very rare and usually have a benign course. In this report, we describe an unusual case of pleomorphic adenoma of the external auditory canal associated with chronic infection of the middle ear.